Synthesis and Characterization of SnO2 Thin Film Semiconductor for Electronic Device Applications - Aris Doyan; Susilawati Susilawati; Kehkashan Alam; Lalu Muliyadi; Firdaus Ali; Mohd Mustafa Awang Kechik (Jurnal Penelitian Pendidikan IPA, 2021)
Synthesis and characterization of SnO2 thin films with various types of doping materials such as aluminum, fluorine and indium have been successfully carried out. This study aims to determine the effect of various types of doping materials on the quality of thin films such as the energy band gap produced. The results showed that the higher the doping concentration, the more transparent the layer formed. In addition, the optical properties of thin films such as band gap energy are affected by the applied doping. The direct and indirect values ​​of the largest band gap energy for the percentage of 95:5% are 3.62 eV and 3.92 eV are found in the SnO2: In thin layer. Meanwhile, the lowest direct and indirect values ​​of band gap energy are in the thin layer of SnO2:(Al+F+In) for a percentage of 85:15%, namely 3.41 eV and 3.55 eV. The greater the amount of doping given, the smaller the bandgap energy produced. In addition, the more combinations of doping mixtures (aluminum, fluorine, and indium) given, the smaller the bandgap energy produced. This shows that the quality of a thin film of SnO2 produced is influenced by the amount of concentration and the type of doping used